Tracking humanitarian funding for reproductive health: a systematic analysis of health and protection proposals from 2002-2013. Issue 1 (December 2015) - Tanabe, Mihoko; Schaus, Kristen; Rastogi, Sonia; Krause, Sandra; Patel, Preeti
Abstract Background The Inter-agency Working Group on Reproductive Health in Crises conducted a ten-year global evaluation of reproductive health in humanitarian settings. This paper examines proposals for reproductive health activities under humanitarian health and protection funding mechanisms for 2002-2013, and the level at which these reproductive health proposals were funded. Methods The study used English and French health and protection proposal data for 2002-2013, extracted from the Financial Tracking Service (FTS) database managed by the United Nations Office for the Coordination of Humanitarian Affairs. Every project was reviewed for relevance against pre-determined reproductive health definitions for 2002-2008. An in-depth analysis was additionally conducted for 2009-2013 through systematically reviewing proposals via a key word search and subsequently classifying them under designated reproductive health categories. Among the relevant reproductive health proposals, counts and proportions were calculated in Excel based on their reproductive health components, primarily by year. Contributions, requests, and unfunded requests were calculated based on the data provided by FTS. Results Among the 11, 347 health and protection proposals issued from 345 emergencies between 2002 and 2013, 3, 912 were relevant to reproductive health (34.5%). The number of proposals containing reproductive health activities increased by an average of 21.9% per year, while the proportion of health and protection sector appeals containing reproductive health activities increased by an average of 10.1% per year. The total funding request over the 12 years amounted to 4.720 billion USD, of which 2.031 billion USD was received. Among reproductive health components for 2009-2013 proposals, maternal newborn health comprised the largest proportion (56.4%), followed by reproductive health-related gender-based violence (45.9%), HIV/sexually transmitted infections (37.5%), general reproductive health (26.2%), and lastly, family planning (14.9%). Conclusion Findings show that more agencies are responding to humanitarian appeals by proposing to implement reproductive health programs and receiving increased aid over the twelve year period. While such developments are welcome, project descriptions show comparatively limited attention and programming for family planning and abortion care in particular.